Strategi Transformasi Digital Di Perguruan Tinggi Indonesia Mandiri Menuju Era Society 5.0 - Aziz Ma'sum Aziz; Eris Dwi Purnama Purnama; Taufik Ridwan; Azhari Ali Ridha; Ade Andri Hendriadi; Ahmad Khusaeri; Apriade Voutama; Iqbal Maulana (Yayasan Pemimpin Inovasi Science, 2026)
Digital transformation in higher education is a strategic necessity in facing the era of Society 5.0, which requires the integration of advanced technology with human-centered values. This study aims to formulate a contextual and adaptive digital transformation strategy through a literature review and conceptual analysis, using the TOE (Technology, Organization, Environment) framework. Data were collected from national and international journals, academic books, and policy documents related to higher education and digital society. The findings reveal that the success of digital transformation is determined by three key dimensions: (1) technology, which includes IT infrastructure, academic information systems, and digital learning platforms; (2) organization, which involves visionary leadership, innovative culture, and digital competencies of human resources; and (3) environment, which encompasses government policies, financial support, and strategic partnerships. The literature synthesis results in a digital transformation strategy model that is adaptive and tailored to the specific context of each institution. A practical implementation is demonstrated through the use of the Learning Management System (LMS) at STMIK IM Perguruan Tinggi Indonesia Mandiri, reflecting the institution’s readiness for the Society 5.0 era. This study is expected to serve as an initial reference for higher education institutions in formulating sustainable, inclusive, and competitive digitalization policies.